Long-Term Follow-Up and Optimization of Interleukin-1 Inhibitors in the Management of Monogenic Autoinflammatory Diseases: Real-Life Data from the JIR Cohort - Hentgen, Véronique; Koné-Paut, Isabelle; Belot, Alexandre; Galeotti, Caroline; Grateau, Gilles; Carbasse, Aurelia; Pagnier, Anne; Pillet, Pascal; Delord, Marc; Hofer, Michael; Georgin-Lavialle, Sophie (Frontiers in Pharmacology, 2021)
Methods: In order to better understand the use of IL1 inhibitors in a real-life setting, our study assessed the dosage regimens of French patients with one of the four main hereditary recurrent fever syndromes (FMF, TRAPS, CAPS and MKD). The patients were retrieved retrospectively from the JIRcohort, an international platform gathering data of patients with pediatric inflammatory diseases. Results: 45 patients had received at least once an IL1 inhibitor (anakinra or canakinumab). Of these, 43% received a lower dosage than the one suggested in the product recommendations, regardless of the type of the IL1 inhibitor. In our cohort none of the FMF or TRAPS patients received an intensified dose of IL-inhibitor. On-demand treatment with a short half-life IL-1 inhibitor has also been used successfully for some patients with one of these 2 conditions The standard dose was given to 42% of the patients; whereas an intensified dose of IL-1 inhibitors was given to 15% of the patients (44% of CAPS patients and 17% of MKD patients). In our cohort each individual patient’s need for treatment seemed highly variable, ranging from on demand treatment regimens to intensified dosage maintenance therapies depending on the activity and the severity of the underlying disease. Conclusion: IL-1 inhibitors are a good treatment option for patients with a hereditary recurrent fever syndrome, but the individual need of the dosage of IL-1 inhibitors to control the disease effectively seems highly variable and depending on severity, activity but also the type of the underlying disease.